Sustainable synthesis and characterization of silver nanoparticles through Juncus acutus flowers and evaluation of their ability to detect NO2 and NH3 gases - Mohammed B. AbdulWahid; Osama H. Abdullah; Othman Hamad Farhan; Maytham Imad Ahmed; Ahmed Mishaal Mohammed; Yousif Hendi Khalaf (Results in Materials)
In this effort, the Juncus acutus plant's flowers were used to create silver nanoparticles (AgNPs). Using X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), and energy dispersive X-ray (EDX), the characteristics of the prepared silver nanoparticles were evaluated. The size of the silver nanoparticles was 38.40 nm. At various temperatures and times, the silver nanoparticles were assessed as gas sensors for the gases NO2 and NH3. At 100 °C, the highest sensitivity response to NO2 gas was 15.09 %. However, in the case of the NH3 gas, the highest sensitivity response was 25 % at 200 °C. For NO2, the sensor displayed the smallest response and recovery times at various temperatures: 19.71s at 300 °C and 33.3s at 100 °C, respectively, and for NH3 gas, 16.74s at 200 °C and 20.25s at 300 °C, respectively. These outcomes highlight the sensor's exceptional response and recovery abilities.